SIDE EFFECTS OF THE 2009 NOMINAL EXCHANGE RATE VOLATILITY IN MEXICAN REMITTANCES´ PURCHASING POWER - Guzman, Gerardo Reyes; Garcia, Carlos Moslares; Munoz, Marcela Ibarra (European Scientific Journal, ESJ, 2013)
The Great Recession emerged as an usual world macroeconomic imbalance, determined by an exchange rate volatility and severe setbacks in international trade, foreign direct investment and flow of labor force. As Western countries tackle their high fiscal deficit and public debt problems, they face historical levels of unemployment. That has made them constrain international immigration, both legal and illegal. Mexico has experienced in this context a fall in remittances as well as in the number of workers leaving for the USA. On the other hand, exchange rate volatility has affected purchasing power of the remittances´ recipient families, making them supposedly better off when the MXN depreciates. In order to estimate the net changes in purchasing power, incomes coming from remittances have to be matched with domestic prices, especially of those items which households consume the most.